Inducible and tissue-specific expression of human C-reactive protein in transgenic mice. - Ciliberto, G (1987)
C-reactive protein (CRP) is a major acute phase reactant in man but not in mouse. It is synthesized in abundant quantities by human hepatocytes during the course of several diseases, mainly acute inflammations. To investigate the regulation of CRP expression, the human CRP gene was introduced into fertilized eggs by microinjection and transgenic mouse lines were derived. The CRP gene is exclusively transcribed in the liver and expression is strictly dependent on experimental inflammation. The kinetics of induction both for RNA and protein synthesis is very fast; RNA is first detectable after 2 h in the liver, the protein after 6 h in the serum. Human CRP levels in the sera of transgenic mice are comparable to those observed in human diseases. Nuclear run-on experiments indicate that regulation is primarily at the transcriptional level.